Right to the city or right to park a car? Acceptability of parking management for a social-ecological transformation of urban neighbourhoods - Baumgartner, Annabell; Klinner, Nora; Lanzendorf, Martin (Transportation research. Part A, Policy and practice, 2025)
•An integrated model is developed to assess the acceptability of parking policies.•Residents support a conversion of on-street parking into cycling lanes and greenery.•Residents support parking fees when combined with parking permits and pull measures.•Psychological factors strongly influence the acceptability of parking policies.•A perceived right to park cars in public space persists in urban neighbourhoods. Public space in urban neighbourhoods is scarce and has to meet a multitude of different demands, triggering conflicts between residents due to diverse needs and preferences. For instance, bottom-up initiatives aligned with the Right to the City movement express strong claims to reassign inefficiently used public space (e.g., on-street car parking). In their view, these areas should be collectively designed and used. At the same time, other residents demand the right to park cars on their streets and at no cost. This study aims to assess the acceptability of parking-related measures that contribute to the social-ecological transformation of urban areas. By conducting a quantitative study (N = 821) in four residential neighbourhoods in Frankfurt am Main, Germany, we analysed the acceptability of different parking policy measures, the factors explaining the public support of these measures, and the implications of our findings on the Right to the City discourse and the implementation of related policies. Our results indicate that despite push measures (e.g., parking fees) being substantially less popular than pull measures, the combination of both (e.g., the conversion of on-street parking into alternative land uses) can receive high levels of support from residents. An integrated model for predicting acceptability is proposed based on psychological factors (the strongest noted impact) but also on travel practices and the neighbourhood’s built environment. Our results are relevant to urban planning practice, indicating strong social support for a reallocation of public street space as long as local needs are considered. The findings emphasise the importance of participative and inclusive rather than top-down approaches in transport planning. Such efforts can negotiate between dissenting voices in society more effectively, re-politicise implementation processes and strengthen the citizens’ Right to the City when transforming urban areas.